2021
DOI: 10.30684/etj.v39i9.841
|View full text |Cite
|
Sign up to set email alerts
|

Hot Spot Analysis of Photovoltaic Module under Partial Shading Conditions by Using IR-Imaging Technology

Abstract:  Output power losses of PV module during irradiance transitions were studied.  The maximum output power loss of PV module under hot spot was around 52.86%.  The temperature difference between the hottest and cooled cell was about 6°C.The probable appearance of localized overheating (hot spot) represents one of the main matters for the reliability and safety of c-Si cells. It entails both a risk for the photovoltaic module's lifetime and a decrease in its operational efficiency. Partial shading is the most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…soiling and dust [31], shading by stationary or changing/moving objects e.g. vegetation [30,32], chimneys, high voltage lines [33], poles, partial shading [32].…”
Section: Failure Modes In Ir-imagingmentioning
confidence: 99%
“…soiling and dust [31], shading by stationary or changing/moving objects e.g. vegetation [30,32], chimneys, high voltage lines [33], poles, partial shading [32].…”
Section: Failure Modes In Ir-imagingmentioning
confidence: 99%
“…A shaded cell under hot-spot conditions operating at reverse bias is dissipating power instead of delivering power. It was reported that if the string working current is higher than the short-circuit current of the shaded cell, the terminal voltage of the shaded cell becomes reversely biased [5][6][7][8]. The shaded cell works as a load to dissipate power instead of delivering it and, therefore, operates at abnormally high temperatures [9,10].…”
Section: Introductionmentioning
confidence: 99%